2015
DOI: 10.3892/ol.2015.3770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combination therapy of siRNA targeting growth hormone receptor and 5-fluorouracil in hepatic metastasis of colon cancer

Abstract: The aim of this study was to investigate the effects of small interfering RNA (siRNA) targeting human growth hormone receptor (hGHR) combined with 5-fluorouracil (5-FU) on the hepatic metastasis of colon cancer. The animal model of liver metastases using human SW480 colon cancer cells was established on BALB/c mice and the siRNA interfering plasmid targeting hGHR gene was constructed. The tumor-bearing mice were randomly divided into the saline control, plasmid, growth hormone (GH), 5-FU, 5-FU+plasmid and 5-FU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Another study used an animal model to examine the combined effect of SiARN targeting the hGHR growth hormone receptor and 5-fluorouracil on colon cancer metastases. The results of that study showed that this combination reduced the incidence of liver metastasis in colon cancer [174]. A study of 46,027 patients examined metastatic distribution patterns in colon and rectal cancer.…”
Section: Metastasis In Target Organsmentioning
confidence: 99%
“…Another study used an animal model to examine the combined effect of SiARN targeting the hGHR growth hormone receptor and 5-fluorouracil on colon cancer metastases. The results of that study showed that this combination reduced the incidence of liver metastasis in colon cancer [174]. A study of 46,027 patients examined metastatic distribution patterns in colon and rectal cancer.…”
Section: Metastasis In Target Organsmentioning
confidence: 99%
“…As a potential strategy to overcome the side effects of FOLFOX or FOLFIRI, application of RNAi has been suggested to treat CLM. Indeed, several studies have demonstrated prevention of micrometastases and metastatic growth of CRC in the liver. Although the results showed promising potential for treatment of CLM, translation of RNAi-based therapies toward clinical settings poses challenges, including intrinsic poor serum stability and nonspecific uptake into biological systems, suggesting a need for the development of efficient delivery systems …”
mentioning
confidence: 99%
“…This compound was shown to be efficient in various tumour types 62 , 63 , 64 , 65 , 66 and to potentiate chemotherapy efficacy. 67 However, its poor passage across the blood–brain barrier 68 predicts low efficacy for GBM treatment. Other GHR‐targeted compounds currently in clinical development such as antisense oligonucleotides 69 could constitute a promising approach, although the capacity of such molecules to reach the brain remains to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Pegvisomant is an efficient PEGylated GH core‐based peptide antagonist currently used in the clinics to counteract excess of GHR signalling in acromegalic patients. This compound was shown to be efficient in various tumour types 62–66 and to potentiate chemotherapy efficacy 67 . However, its poor passage across the blood–brain barrier 68 predicts low efficacy for GBM treatment.…”
Section: Discussionmentioning
confidence: 99%